The Quest for a Poetics of Goodness in Plato and Aristotle (2012)
The paper, which compares Plato and Aristotle’s different approaches towards artistic activity, is divided into three parts. The first part discusses Plato’s Ion on mimesis and technē, as well as the role that poetry plays in the Republic. The second section offers an account of Aristotle’s idea of happiness as the end of action. Thelast section of this study deals with an attempt to reconcile Plato and Aristotle’s attitude towards mimetic art in a treatise by a Neoplatonic renaissance thinker, Torquato Tasso.